Study of GSM based passive radar system - Tan, Danny Kai Pin. (2008)
Study and access the feasibility and suitability of using the GSM downlink signal from the GSM base station transmitter as the transmissions of opportunity. It also describes the research and development of a totally independent low-cost experimental GSM based passive radar system in Nanyang Technological University.